Research of an Improved BP Decoding Algorithm - Guoqiang Wu; Zhaowei Sun (IEEC 2009 : The First International Symposium on Information Engineering and Electronic Commerce : proceedings : 16-17 May 2009, 2009)
That the computation load is big is a shortcoming of traditional BP decoding algorithm. According to this shortcoming we give an improved BP decoding algorithm. The decoding algorithm in the iterative decoding process, only need to update the possibility of a wrong bit of information without having to update the information whose reliability is very high, raises the decoding efficiency and reduces decoding time delay. The simulation result shows: the calculation load of improved BP decoding algorithms descends distinctively with the increasing iteration numbers; Along with the times increasing of LDPC code iterations upper limit, coding performance can be obviously improved.